Stereotactic Radiosurgery in the Management of Limited (1-4) Brain Metasteses: Systematic Review and International Stereotactic Radiosurgery Society Practice Guideline. Issue 3 (3rd November 2017) - Chao, Samuel T; De Salles, Antonio; Hayashi, Motohiro; Levivier, Marc; Ma, Lijun; Martinez, Roberto; Paddick, Ian; Régis, Jean; Ryu, Samuel; Slotman, Ben J; Sahgal, Arjun
Abstract: BACKGROUND: Guidelines regarding stereotactic radiosurgery (SRS) for brain metastases are missing recently published evidence. OBJECTIVE: To conduct a systematic review and provide an objective summary of publications regarding SRS in managing patients with 1 to 4 brain metastases. METHODS: Using Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines, a systematic review was conducted using PubMed and Medline up to November 2016. A separate search was conducted for SRS for larger brain metastases. RESULTS: Twenty-seven prospective studies, critical reviews, meta-analyses, and published consensus guidelines were reviewed. Four key points came from these studies. First, there is no detriment to survival by withholding whole brain radiation (WBRT) in the upfront management of brain metastases with SRS. Second, while SRS on its own provides a high rate of local control (LC), WBRT may provide further increase in LC. Next, WBRT does provide distant brain control with less need for salvage therapy. Finally, the addition of WBRT does affect neurocognitive function and quality of life more than SRS alone. For larger brain metastases, surgical resection should be considered, especially when factoring lower LC with single-session radiosurgery. There is emerging data showing good LC and/or decreased toxicity with multisession radiosurgery. CONCLUSION: A number of well-conducted prospective and meta-analyses studies demonstrate good LC, without compromising survival, using SRS alone for patients with a limited number of brain metastases. Some also demonstrated less impact on neurocognitive function with SRS alone. Practice guidelines were developed using these data with International Stereotactic Radiosurgery Society consensus.